ASSESSMENT OF EDUCATION QUALITY IN COMPREHENSIVE SCHOOL: THE ATTITUDE OF TEACHERS AND PUPILS - Gedminienė, Daiva; Gumuliauskienė, Aušrinė (Acta Paedagogica Vilnensia, 2008)
Quality of the educational system became the EU priority aim when highlighting the tendencies of internalisation of education. While undergoing increase of responsibility of every educational institution and its community members for educational quality, self-assessment of school helps to reveal knowledge of its community on internal processes from contribution to result, perception of one’s institution as the whole, formation of the philosophy of monitoring and assessment of the educational process, the culture of quality. Quality assessment of an educational institution is a multiple one and it has a number of purposes. Assessment based on attitude of participants of the educational process is significant because it complements conclusions of internal and external audit, provides opportunities for a more thorough analysis of the state of institution’s quality of activities, makes the feedback among participants of the educational process effective, helps in self-development of reflection abilities, can benefit to discussion among school community on conception, standards, optimisation methods, etc. of quality. Exchange of attitudes as well as dialogue within school community should be a permanent process. The research has proved that obvious differences between teachers and pupils, conception and perception of significance of educational quality exist in the gymnasium. The most pronounced differences in assessment of educational quality became highlighted in assessment of various aspects of the process of teaching and learning: purposefulness of organisation of the process of teaching and learning, attractiveness, the level of mastering of the content of teaching and learning, effectiveness of feedback, purpose and significance of homework tasks, encouragement of activeness and progress of pupils, assessment of teaching and learning achievements, school’s capacity to meet the needs of the learners.
Keywords: education quality; educational process; assessment; attitude; factors